Revolutionary Trends in Indian History: Ideological Diversity and Collective Resistance - Rashid Manzoor Bhat; Silllalee A/L S. Kandasamy (Al-Makki Publisher, 2023)
In this study an attempt has been made to explore the revolutionary trends in India, exploring their ideological diversity, historical contexts, motivations, organisational structures, impact and influence, and forms of collective resistance. The study employs an analytical and exploratory approach, combining historical, and qualitative research methods. It aims to give readers a thorough comprehension of the ever-changing character of Indian revolutionary movements by drawing on a wide variety of primary and secondary sources, as well as archival records. This study aims to chart the ideological terrain, place contemporary events in their proper historical context, examine organisational structures, evaluate the influence and effect of revolutionary movements, and investigate different types of collective resistance. The methodology involves a systematic analysis of scholarly works, historical records, and firsthand accounts. The findings reveal the diverse range of ideological frameworks adopted by revolutionary movements in India, the socio-political conditions shaping their emergence, the motivations behind participation, the organisational strategies employed, the transformative impact on society, and the various forms of collective resistance utilised.